Pivotal Importance of STAT3 in Protecting the Heart from Acute and Chronic Stress: New Advancement and Unresolved Issues - Zouein, Fouad A.; Altara, Raffaele; Chen, Qun; Lesnefsky, Edward J.; Kurdi, Mazen; Booz, George W. (Frontiers in Cardiovascular Medicine, 2015)
The transcription factor Signal Transducer and Activator of Transcription 3 (STAT3) has been implicated in protecting the heart from acute ischemic injury under both basal conditions and as a crucial component of pre- and post-conditioning protocols. A number of anti-oxidant and antiapoptotic genes are upregulated by STAT3 via canonical means involving phosphorylation on Y705 and S727, although other incompletely defined posttranslational modifications are involved. In addition, STAT3 is now known to be present in cardiac mitochondria and to exert actions that regulate the electron transport chain, reactive oxygen species (ROS) production, and mitochondrial permeability transition pore (mPTP) opening. These non-canonical actions of STAT3 are enhanced by S727 phosphorylation. The molecular basis for the mitochondrial actions of STAT3 are poorly understood, but STAT3 is known to interact with a critical subunit of complex I and to regulate complex I function. Dysfunctional complex I has been implicated in ischemic injury, heart failure, and the aging process. Evidence also indicates that STAT3 is protective to the heart under chronic stress conditions, including hypertension, pregnancy, and advanced age. Paradoxically, the accumulation of unphosphorylated STAT3 (U-STAT3) in the nucleus has been suggested to drive pathological cardiac hypertrophy and inflammation via noncanonical gene expression, perhaps involving a distinct acetylation profile. U-STAT3 may also regulate chromatin stability. Our understanding of how the noncanonical genomic and mitochondrial actions of STAT3 in the heart are regulated and coordinated with the canonical actions of STAT3 is rudimentary. Here we present an overview of what is currently known about the pleotropic actions of STAT3 in the heart in order to highlight controversies and unresolved issues.